2006
DOI: 10.2220/biomedres.27.75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retinoic acid-induced transglutaminase on cell growth in regenerating liver

Abstract: Transglutaminase 2 (TG2) is implicated in the inhibitory regulation of the hepatocyte growth in vitro. In vivo, however, the role of TG2 in liver regeneration after partial hepatectomy (PH) is almost unknown. A dramatic increase of TG2 expression and activation is induced by retinoic acid (RA). Here we show the effect of the RA-induced overexpression of TG2 on liver regeneration after PH. Regenerating rat liver was prepared by 70% PH. RA was intraperitoneally injected immediately after PH. TG2 activity was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…An in vitro study found that RA inhibited DNA synthesis in rat hepatocytes (Ikeda & Fujiwara, ). This result is consistent with an in vivo study, showing repression of proliferation upon RA treatment (Ohtake, Maruko, Abe, Fukumoto, & Ohkubo, ). However, RA was shown to have a mitogenic effect in other studies that utilized hepatocytes cultured upon liver resection (Ledda‐Columbano et al, ; You et al, ).…”
Section: Wound Signaling and The Regulation Of Proliferationsupporting
confidence: 92%
“…An in vitro study found that RA inhibited DNA synthesis in rat hepatocytes (Ikeda & Fujiwara, ). This result is consistent with an in vivo study, showing repression of proliferation upon RA treatment (Ohtake, Maruko, Abe, Fukumoto, & Ohkubo, ). However, RA was shown to have a mitogenic effect in other studies that utilized hepatocytes cultured upon liver resection (Ledda‐Columbano et al, ; You et al, ).…”
Section: Wound Signaling and The Regulation Of Proliferationsupporting
confidence: 92%
“…Early in vitro studies reported that RA is a potent inhibitor of DNA synthesis in primary rat hepatocytes (9). Similarly, when administered after PH, RA disrupted rat hepatocyte proliferation in vivo by repressing early response genes and increasing the activity of transglutaminase and ornithinedecarboxylase (1014). In contrast to these findings, other studies have shown that RA enhances hepatocyte proliferation and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor to consider is the timing of exogenous RA administration. In the previous studies, RA was administered after surgical resection of the liver (1014, 18). The hepatoprotective role of RA preconditioning has recently been proposed in an ischemic/reperfusion injury model (20), but there is no evidence in the literature that clearly documents the effects of RA treatment prior to PH-induced liver regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…A study in rats [25] and other studies have confirmed the role of retinoic acid in the expression of TG-1 [26] and TG-2 [27]. Because TG-1 has a role in ocular surface keratinization, some studies have focused on other upstream triggers of TG-1 including interferon gamma (IFN-γ) [28].…”
Section: Discussionmentioning
confidence: 99%